Controlling electron recollision with combined linear and circular polarization - Ben, Shuai; Han, Yifan; Yang, Weifeng; Yu, Weiwei; Hao, Xiaolei; Song, Xiaohong; Li, Weidong; Chen, Jing (Frontiers in Physics, 2022)
We theoretically investigate the non-sequential double ionization of Ar atoms in the combined fields of linearly polarized laser and circularly polarized laser through 3D semiclassical simulations. By partially overlapping the two time-delayed multicycle laser pulses, we construct an optical waveform whose polarization ellipticity increase slowly for consecutive optical cycles. This composite laser pulses with the time-dependent ellipticity can tunnel-ionize atoms and steer the first tunneling electron to recollision with the second bound electron through different trajectories, in which the recollision occurs with different return times of the first ionized electron. Through tuning delay time between the two laser pulses, the double ionization yields and recollision trajectories with different return times can be controlled. The time-dependent ellipticity with different delay time can enhance or suppress the probability of different return times. This work provides a scheme exploring electron dynamics in few optical cycle or even subcycle time scale in a multicycle laser field without having to be limited to near-single-cycle laser pulses.